KÜÇÜK GÜÇLÜ HİDROELEKTRİK SANTRALLERDE DÜŞÜ, DEBİ, YÜK VE VERİM İLİŞKİLERİ - ÖZDEMİR, MAHMUT TEMEL (Fırat Üniveristesi, 2002)
Yüksek Lisans Tezi KÜÇÜK GÜÇLÜ HİDROELEKTRİK SANTRALLERDE DÜŞÜ, DEBİ, YÜK VE VERİM İLİŞKİLERİ Mahmut Temel OZDEMİR Fırat Üniversitesi Fen Bilimleri Enstitüsü Elektrik-Elektronik Mühendisliği Anabilim Dalı 2002, Sayfa: 63 Enerji üretiminde hidroelektrik santrallerin (HES) önemli bir yeri vardır. Ülkemizdeki hidrolik potansiyelin fazla olmasına karşın bu potansiyelin tam olarak kullanılamaması önemli bir eksikliktir. Küçük ve çok küçük HES'lerin yapılıp faaliyete geçirilmesi ile bu eksiklik giderilebilir. Böylece, tam olarak kullanılamayan hidrolik potansiyelimiz değerlendirilerek ekonomiye önemli katkı sağlanabilir. Bu çalışmada, Türkiye'nin hidrolik potansiyeli, küçük ve çok küçük HES' ler ile bu HES'lerde kullanılan türbinler hakkında bilgi verilmiştir. Hidrolik türbinlerin debi, düşü, verim ve yük ilişkilerini belirlemek amacıyla Pelton, Francis ve Cross-Flow türbinlerinin modelleri oluşturulmuştur. Oluşturulan modeller yardımıyla ve MATLAB Programı kullanılarak, bu türbinlerin bilgisayar benzetimi yapılmıştır. Elde edilen sonuçlar, önceki çalışmalar dikkate alınarak irdelenmiştir. ANAHTAR KELİMELER: Küçük ve Çok Küçük HES, Hidrolik Türbin, Hidrolik Türbin Modeli, Düşü, Debi, Verim DC

SUMMARY Master Thesis RELATION AMONG HEAD, FLOW, LOAD AND EFFICIENCY ON THE SMALL HYDROELECTRIC POWER PLANT Mahmut Temel ÖZDEMİR Firat University Graduate School of Natural and Applied Sciences Department of Electrical and Electronics Engineering 2002, Page: 63 Hydroelectric power plants (HPP) have a considerable position in the energy production. In our country, there is a big hydraulic potential which is not used exactly, is an important deficiency. This absence can be remove with building and entering to activity the mini and micro Hydroelectric Power Plants. Thus, with utilizing hydraulic potential which is not used completely, can supply a big assistance to economy. This study gives information about Turkiye's hydraulic potential, mini and micro HPP and turbines which are used in this Hydroelectric Power Plants. It is aimed to determine the relation of flow rate, head, efficiency and load of this hydraulic turbines and forming the models of Pelton, Francis and Cross-Flow turbines. These turbines simulations have been done using those formed models and MATLAB program. The obtained results have been examined with taking into considerations the previous studies. Key Words: Mini and Micro HPP, Hydraulic Turbine, Hydraulic Turbine Model, Flow Rate, Head, Efficiency X
Relations among head, flow, load and efficiency on the small hydroelectric power plant
Keywords: Elektrik ve Elektronik Mühendisliği; Electrical and Electronics Engineering